Pengaruh Promosi Penjualan Dan Kualitas Pelayanan Terhadap Loyalitas Konsumen Pada PT. Exzer Amsal Mandiri - Anselmusdeli Lugu; ahmad yudhira; khamo waruwu (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2022)
The purpose of this research is to find out partially or simultaneously the effect of sales promotion and service quality on consumer loyalty at PT. Independent Proverbs Exzer. PT. Exzer Amsal Mandiri is engaged in the field of medical devices (specially marketing liquid disinfectant products) to hospitals. This research is a descriptive quantitative questionnaire instrument. The research population was 36 hospitals with a saturated sample technique, the sample was 36 people. The results of the study are the tcount value of sales promotion is 6.168, the value of ttable is 1.692; the value of tcount > ttable and sigcount < sigtable (6.168 > 1.692) and (0.000 < 0.05). The tcount value of service quality is 2.141, the t-table value is 1.692; the value of tcount < ttable and sigcount < sigtable (2.141 > 1.692) and (0.000 < 0.05). The value of Rsquare is 0.611 or R2x 100% is 61.10%, meaning that the independent variable makes a big contribution to describe customer loyalty as much as 61.10%, the remaining 38.90% is influenced by other factors.